2008
DOI: 10.1080/08998280.2008.11928404
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafts Placed Around Temporomandibular Joint Total Joint Prostheses to Prevent Heterotopic Bone Formation

Abstract: This study evaluated 1) the efficacy of packing autologous fat grafts around temporomandibular joint (TMJ) total joint prosthetic reconstructions to prevent fibrosis and heterotopic bone formation and 2) the effects on postsurgical joint mobility and jaw function. One hundred fifteen patients (5 males and 110 females) underwent TMJ reconstruction with total joint prostheses and simultaneous fat grafts (88 bilateral and 27 unilateral) for a total of 203 joints. The abdominal fat grafts were packed around the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 12 publications
0
44
0
6
Order By: Relevance
“…It has also been reported that replacement of the affected TMJ prosthesis with packing of autologous fat around the joint components reduces the risk of re-ankylosis by reducing dead-space available for hematoma formation and subsequent ossification [28] [29] [30]. Fat not only fills the dead space around the TMJR articulating components but also has a haemostatic effect on the surrounding tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that replacement of the affected TMJ prosthesis with packing of autologous fat around the joint components reduces the risk of re-ankylosis by reducing dead-space available for hematoma formation and subsequent ossification [28] [29] [30]. Fat not only fills the dead space around the TMJR articulating components but also has a haemostatic effect on the surrounding tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Viable condition of fat tissues even after years at the joint region are studied and proved by many authors. [6,7,14,16,17] The surgeons who used the dermal fat graft as the interposition material for the management of TMJ ankylosis uniformly claimed the minimal fibrosis action and hetarotopic calcification prevention [8,14] as the advantages of using dermis fat graft. Some authors also practiced with the buccal pad fat [15,16] as the interposition material and uniformly claimed the material, buccal pad fat, was taking appreciable part in the prevention of reankylosis .…”
Section: Discussionmentioning
confidence: 99%
“…They have stated that the intermittent compressive forces of the joint may act as a negative influence on the growth and also explained the fat tissues are maintained within the joint space itself. Larry M Wolford et al in 2008, [8] in their study of fixing prosthesis in the joint space have not encountered any fibrosis or bone formation. Mehothra et al in 2008 [9] randomly divided 17 patients in to 2 groups, the first group was treated with dermis fat graft procured from the groin where as the controlled group treated with temporalis fascia.…”
Section: Introductionmentioning
confidence: 93%
“…Wolford has described a reduction in frequency of recurrence when an alloplastic reconstruction is used in conjunction with abdominal free fat packed around the prosthesis. 20 Once recurrence has occurred with an autogenous reconstruction the host bed is so poorly vascularised that only a vascularised graft or alloplast should be used.…”
Section: Ankylosismentioning
confidence: 99%